Identifikasi Penanda Masak Fisiologis untuk Panen Benih Mentimun (Cucumis sativus L.) - I PUTU EGA ANTARA; ANAK AGUNG MADE ASTININGSIH; ANAK AGUNG GEDE SUGIARTA (Agrotrop : Journal on Agriculture Science, 2023)
Identification of Physiological Cooking Markers for Cucumber (Cucumis sativus L.) Seed Harvest. Cucumber (Cucumis sativus L.) has a wide adaptability to the environment. Cucumber production in Indonesia has decreased every year. The availability of quality seeds is one of the important factors in increasing the productivity of cucumber plants. This study aims to identify physiological ripening markers, especially in cucumber fruit. This study used a one-factor randomized block design method with 4 levels of treatment at harvesting age of cucumbers, namely 24, 27, 30, and 33 days after flower blooming. The variables observed in this study were; a) identification of fruit and seed maturity markers; 1) fresh weight of fruit (g), 2) fresh weight of 100 seeds (g), 3) oven dry weight of 100 seeds (g), 4) seed moisture content (%), and 5) fruit color development; b) testing of seed quality; 1) seed germination (%) and 2) seed germination vigor (%).The results showed that the right harvest time based on the character of the fruit and seeds to produce quality seeds for cucumber plants was 27 days after the flowers bloom. The character of the fruit at that time was shiny green with a yellow tinge and reached the maximum fresh weight, while the character of the seeds at that time was bright yellow seeds, with a fresh weight of 100 seeds was 3,95g and an oven dry weight of 100 seeds was 1,51g reaching the maximum weight. And seed moisture content at the age of 27 with the lowest percentage. The quality of cucumber seeds harvested when physiologically ripe was obtained with the highest average values such as seed germination (93.17%) and simultaneous growth vigor (81.83%).